Child Immunization in Pakistan: Socio-Institutional and Regional Aspects - Khan, Rana Ejaz Ali; Aslam, Iqra (Asian Journal of Economic Modelling, 2016)
This paper attempted to examine the socioeconomic determinants of preventive measures of child health, i.e. child immunization, particularly focusing on the factors of social institutions and regional diversity in Pakistan economy. For the purpose micro data having 8731 observations from Pakistan Demographic Health Survey (PDHS) 2006-2007 has been utilized. Binary logistic regression is employed to determine the association between complete immunization of children (in the age group of 12 months to 5 years) and explanatory variables. The ethnicity of the households has been taken as proxy of social institution and provinces of Pakistan as regional diversity. Complete immunization of children is captured by basic vaccinations, i.e. BCG, Measles, DPT and Polio. A child is assumed as completely immunized if he/she has received all the twelve vaccinations. The results have shown that social institution represented by ethnicity of household has significant impact on the probability of immunization of children. The children of Urdu, Sindhi, Pashtu and Barohi speaking families are less likely to be immunized as compared to those of Punjabi speaking families. The children from Pashto speaking families are least likely to be immunized as compared to children from Punjabi speaking families. The children living in Sindh and Balochistan are least likely to have complete immunization as compared to those living in Punjab. The results have further shown that male children and children born in hospitals are more likely to be immunized. The probability of complete immunization of children increases with increase in educational level of mother. The children of working mothers are less likely to be completely immunized as compared to their counterparts of mothers who are not working.